DETERMINANT OF CONSUMER DECISION ON ISLAMIC BANKING - Dian Novita Sari; Siswanto Siswanto; Ikhsan Maksum; Fadlil Abdani; Ryan Basith Fasih Khan; Nora Ria Retnasih; Setiani Setiani; Masyhuri Masyhuri (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2023)
This study investigates the determinant of customer decisions in Islamic banks' savings: motivation, promotion, and religiosity. Trust variable as a form of research novelty as a mediation. This study uses a quantitative approach with explanatory research. Using purposive sampling, the sample is 95 Islamic bank customers in Nganjuk City, East Java. Data are analyzed using structural equation modeling with Smartpls software. This research generally describes the factors that can improve customer decisions in opening savings at Islamic banks, such as motivation, promotion, and religiosity. These three factors in this study proved that only direct motivation could improve customer decisions. The result means that the other two factors need a mediating variable in the form of customer trust in Islamic banks regarding the safety of money stored and guarantees free from usury. These findings can be a suggestion for the management of Islamic banks to do promotions more often, meaning that what has been done now is still inferior to conventional banks in promotion.